PENGARUH FAKTOR-FAKTOR KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN IKLAN DI GADJAH MADA ENTERPRISE - Ana Fitriyatul Bilgies; Arifah Sundari; Nurul Fauziyah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
This research is one of the methods used by researchers to determine the level of customer satisfaction that has customer loyalty with various marketing methods that are carried out to provide the number of components that influence consumer loyalty attitudes. In this study also makes the four variables represent some expanded customer satisfaction: Intensifly, and Cross selling. Results of this research,obtained that the cross selling variable provides the biggest contribution to consumer loyalty.